PEMBUATAN KARTU INDEKS SEBAGAI MEDIA DALAM MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE (ETH) - Allo Linggi, Novriyani; Gustina, Gustina; Paramita, Ielda (Universitas Tadulako, 2022)
This research was conducted to produce an index card using a 4-D model. Making the index card is expected to be able to assist students in self-study in understanding dynamic fluid physics concepts and guide students to be more active in the learning process. This study refers to the Four-D (4-D) model which includes 4 stages namely Define, Design, Development, and Disseminate. The subjects of this study were 13 students of Class XI MIA 8. To determine the feasibility level of the index card, product validation was carried out. The validation which was carried out on the product is divided into three which are material feasibility test, media feasibility test, and limited trial on research subjects. Based on the material expert validation, the average score is 3.39 which is categorized as